The effects of storage temperature and time on the levels of phthalates in commercial PET-bottled water - Syazwan Razali, Nur Amira; Ungku Zainal Abidin, Ungku Fatimah; Zainal Abedin, Nur Hanani; Omar, Syaliza; Selamat, Jinap; Sanny, Maimunah (Universiti Kebangsaan Malaysia, 2021)
This study was conducted to determine the effects of storage temperature and time on the levels of phthalates in commercial PET-bottled water. Freshly-produced water samples consisted of drinking, mineral, and sparkling in PET bottles were collected from a manufacturing site and subjected to different storage temperatures (refrigeration temperature of 4 °C, room temperature of 25 °C, and 40 °C) and times (0 month as control, 1.5 months, 3 months, and 6 months). Six different phthalates were analyzed using LC-MS/MS with deuterated bis(2-ethylhexyl)phthalate (DEHP) as internal standard. DEHP in the PET-bottled water was detected in the range from 2.32 to 27.6 ng/mL for 3- and 6-month storage samples; higher than di-n-octyl phthalate (DnOP) detected in the range from 1.57 to 12.6 ng/mL. Higher levels of DEHP and DnOP in PET-bottled mineral water were detected at room temperature of 25 °C when compared to refrigeration temperature of 4 °C, and 40 °C at 6-month storage. Higher level of DEHP and DnOP in drinking water was found at 6 months compared to 3 months in refrigeration temperature of 4 °C. The pronounced effects of storage temperatures on the levels of phthalates was observed only after 6 months of storage in which DEHP levels exceeded the maximum established limit of 6 ng/mL.